2015
DOI: 10.33073/pjm-2015-010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antibiotics on polymorphonuclear leukocyte functions and myeloperoxidase activity, glutathione and malondialdehyde levels in allergic asthma

Abstract: A b s t r a c tWe investigated the effect of ciprofloxacin, rifampicine and doxycycline on myeloperoxidase (MPO) activity, glutathione (GSH) and malondialdehyde (MDA) levels in allergic asthma patients and healthy volunteers. Polymorphonuclear leukocytes(PMNs) were isolated with ficoll-hypaque gradient centrifugation method. MPO activity was assayed with modified o-dianisidine, GSH by Ellman's and MDA levels by Beuge's method. PMN functions and MDA levels of patients significantly decreased when compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…In the current study, the balance between oxidative and anti oxidative systems was assessed by measuring the serum levels of GSH and MDA. Whereas, GSH is a vital antioxidant that belongs to the non-enzymatic antioxidant defense system and scavenges free radicals directly, while MDA is an indicator of lipid peroxidation that is formed by free radicals during tissue damage, so it is used to measure oxidative stress (15).There was significant decrease in GSH and significant increase in MDA in UC group as compared to the control, and the reverse revealed in RJ group consistent with previous studies [1,3,16] .…”
Section: Discussionsupporting
confidence: 86%
“…In the current study, the balance between oxidative and anti oxidative systems was assessed by measuring the serum levels of GSH and MDA. Whereas, GSH is a vital antioxidant that belongs to the non-enzymatic antioxidant defense system and scavenges free radicals directly, while MDA is an indicator of lipid peroxidation that is formed by free radicals during tissue damage, so it is used to measure oxidative stress (15).There was significant decrease in GSH and significant increase in MDA in UC group as compared to the control, and the reverse revealed in RJ group consistent with previous studies [1,3,16] .…”
Section: Discussionsupporting
confidence: 86%
“…Yu et al found that hydrogen-rich saline improved the serum MDA and SOD levels in an allergic rhinitis animal model [ 23 ] involved with suppression of eotaxin, further confirming that molecular hydrogen had protective effects on allergic disorders. MPO, which is a haemoprotein secreted during activation of neutrophils [ 24 ], was considered to stimulate the production of MDA and participate in neutrophilic airway inflammation in asthma [ 25 ]. The simultaneous decrease of MDA and MPO may suggest the interaction between these two substances.…”
Section: Discussionmentioning
confidence: 99%
“…& Lipid peroxidation was detected by measuring malondialdehyde (MDA) (Rayaman et al 2015). It was measured colorimetrically by a commercially available kit (Biodiagnostic, Cairo, Egypt) according to Lapenna et al (2001).…”
Section: Lipid Peroxidation Estimation and Oxidative Enzyme Assaymentioning
confidence: 99%